An interrupted history of digital divides - Reisdorf, Bianca Christin; Triwibowo, Whisnu; Nelson, Michael; Dutton, William (AoIR Selected Papers of Internet Research, 2016)
In the early days of the Internet, researchers across various fields and disciplines focused on the phenomenon of digital divides and digital inequalities, and this area is reviving as a focus of research. However, with changing proportions of Internet users and non-users and the perception from the Internet shifting from being a new innovation to something that the majority of citizens in North America and Western Europe take for granted come changing foci of investigation and changing questions. In this paper, we will investigate the history of digital divides and inequalities in the United States, with a case study of an ongoing survey of the State of Michigan. Using data sets reaching back to 1997, this paper examines how the very definition and severity of digital divides have evolved over the last twenty years in Michigan and in the US as a whole. The observed changes in the proportion of users and non-users as well as the frequency of use and the way we inquire about digital divides and inequalities can be a powerful and informative tool for understanding not only the history of digital divides, but also remind the research community of the dramatic changes that have occurred in the Internet’s short history in ways that can open up new and old streams of research for understanding digital divides in countries with low or high proportions of Internet users.